CURRENT RATIO, RETURN ON ASSETS, DEVIDEND PAYOUT RATIO PENGARUHNYA TERHADAP HARGA SAHAM: PADA PERUSAHAAN KEUANGAN SEKTOR LAYANAN PERDAGANGAN DAN INVESTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017 – 2021 - Firdaus, Zuchruf; Drs.H.Friyanto,MSA,Ak,CA,CPA,CSRA,CSP,ACPA,CTA,CFRMP,CFRS.; Sudarjo, Sudarjo (Akademika : Jurnal Manajemen, Akuntansi, dan Bisnis., 2025)
The purpose of this research is to examine and analyze the influence of Current Ratio (CR), Return On Assets (ROA), and Devidend Payout Ratio (DPR) on Stock Price in the Trade and Investment Services Sector Financial Companies Listed On Indonesia Stock Exchange 2017 -2021. The stock price is the closing price of the stock market during the observation period for each type of stock sampled and its movements are constantly observed by investors. One of the basic concepts is financial management is that the goal that financial management wants to achieve is to maximize the value of the company. The study aims to determine if Current Ratio has partial significance to Stock Price, Return on Assets has partial significance to Stock Price, Devidend Payout Ratio has partial significance to Stock Price, and Current Ratio, Return on Assets, and Devidend Payout Ratio has significance simultaneous to Stock Price. The sample used is the Trade and Investment Services Sector Financial Companies listed on the Indonesia Stock Exchange 2017 – 2021 period. The population is 12 companies and after the selection process for sample by purposive sampling method making them 6 companies with 5 years observations. The research using the quantitative approach and the data used as secondary from the annual report of companies listed on the Indonesia Stock Exchange and used the Stock Price to measure the quality of the company’s performance. The results of hypothesis testing partially state that the Current Ratio, Return on Assets, Devidend Payout Ratio has a significant effect on the Stock Price. Meanwhile, simultaneous hypothesis testing states that the Current Ratio, Return On Assets, and Devidend Payout Ratio have a significance simultaneous effect on the Stock Price.